Idiomatikal pada Stand Up Comedy Kiky Saputri dan Ate roasting Amin - Lestari, Intan; Rani Ardesi Pratiwi; Reza Pahlevi Ginting (Journal of Practice Learning and Educational Development, 2026)
The purpose of this research is (1) to describe the types of idiomatic expressions found in Kiky Saputri's stand-up comedy roasting Amin, and (2) to describe the idiomatic functions found in Kiky Saputri's stand-up comedy roasting Amin. The data in this research consists of idiomatic expressions found in Kiky Saputri's and Ate's roasting of Amin. The data source in this research is a video on YouTube titled "Kiky Saputri and Ate roasting Amin." The method used in this research is a qualitative method with data collection techniques, (1) listening to and paying attention to the idiomatic expressions found in the roasting video of Amin, (2) noting the idiomatic expressions that have been identified and correspond with the data in the video, (3) transcribing the video to facilitate the data collection process and to prevent missing idiomatic data in the research. Based on the research results that have been conducted, there are 40 data points divided into 9 full idiom types and 33 partial idiom types. In addition, there are also idiom functions. The function as advice appears in 9 data, the function as sarcasm in 23 data, the function as praise in 4 data, and the function as emphasis in 5 data.